1993
DOI: 10.1038/ki.1993.389
|View full text |Cite
|
Sign up to set email alerts
|

Expression of apolipoprotein B epitopes in low density lipoproteins of hemodialyzed patients

Abstract: Serum and isolated low-density lipoprotein (LDL) composition abnormalities were investigated in 20 hemodialyzed patients with chronic renal failure and 15 healthy normolipidemic subjects for comparison. LDL apolipoprotein B (apo B) epitope accessibility was determined by the use of seven monoclonal antibodies (Mabs). These Mabs recognize fragments on the N-terminal part of apo B (Mabs B1, B4), on the middle part (Mab BL7), on the C-terminal (Mabs BA11, BL3), and the two remaining Mabs recognize conformational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…1) and the protein/antigen ratio and the C50 value of the isolated OxLDL were identical to these of standard OxLDL preparations (Table 3). These data suggested that increased immunoreactivity of OxLDL fractions in plasma of these patients depended indeed on the higher extent of protein modification and not on changes in lipid composition as was previously observed with other antibodies (24). The increased electrophoretic mobility, the increased lysine modification, the increased cholesterol/protein ratio, the decreased levels of arachidonic acid and linoleic acid were very similar to these of oxidatively modified LDL extracted from atherosclerotic le sions (25,26).…”
Section: Discussionsupporting
confidence: 77%
“…1) and the protein/antigen ratio and the C50 value of the isolated OxLDL were identical to these of standard OxLDL preparations (Table 3). These data suggested that increased immunoreactivity of OxLDL fractions in plasma of these patients depended indeed on the higher extent of protein modification and not on changes in lipid composition as was previously observed with other antibodies (24). The increased electrophoretic mobility, the increased lysine modification, the increased cholesterol/protein ratio, the decreased levels of arachidonic acid and linoleic acid were very similar to these of oxidatively modified LDL extracted from atherosclerotic le sions (25,26).…”
Section: Discussionsupporting
confidence: 77%
“…Such lipoproteins are easily subject to oxidative modification by the generated free radicals, hindering their recognition by the apo B-E receptors in the liver cell, but taken up rapidly by the kidney. 26 This probably explains the significant accumulation of lipids in the kidney cortices of the cisplatin+spironolactone-induced nephrotic animals, with lower hepatic cholesterol content.…”
Section: Discussionmentioning
confidence: 99%
“…32 LDL, modi®ed by its oxidation, was also suggested to contribute in the dyslipidaemia and progression of glomerulosclerosis. The modi®ed LDL was less effectively recognized by the B/E receptor of the cell for its uptake, 33 but rapidly taken up by macrophages to generate foam cells which play an important pathogenic role in focal segmental glomerulosclerosis and atherosclerosis. 34 Oxidation of LDL can occur as a consequence of lipid peroxidation caused by increased free radical production as demonstrated in uraemic patients, 35 and in drug-induced nephrotic animals.…”
Section: Discussionmentioning
confidence: 99%